Growth, optical, electrical and photoconductivity studies of a novel nonlinear optical single crystal: Mercury cadmium chloride thiocyanate. Issue 1 (17th February 2015) - Kumar, S M Ravi; Selvakumar, S; Sagayaraj, P; Anbarasi, A
Abstract: SCN − ligand based organometallic non-linear optical mercury cadmium chloride thiocyanate (MCCTC) crystals are grown from water plus methanol mixed solvent by slow evaporation technique. The grown crystals are confirmed by single crystal X-ray diffraction analysis which reveals that the MCCTC belongs to rhombohedral system with R3c space group. MCCTC exhibits a SHG efficiency which is nearly 17 times more than that of KDP. The dielectric constant, dielectric loss measurements of the sample have been carried out for different frequencies (100 Hz to 5 MHz) and, temperatures (308 to 388 K) and the results are discussed. Photoconductivity study confirms that the title compound possesses negative photoconducting nature. The surface morphology of MCCTC was also investigated